The Price of Loyalty - Suskind, Ron (London Free Press, 2004)
An explosive, authoritative insider account of the workings - or non-workings - of George W Bush's White House; shocking, gripping, timely
Include Index and Epilouge
Keywords: United States -- Politics and government -- Bush, George W. (George Walker), 1946-